(untitled) (مجلة إحالات, 2026)
This research revolves around the study of the mystical phenomenon in the Diwan of Memory of Rhymes by the Lebanese poet Nizamuddin Fadlallah, as it seeks to highlight the manifestations of the Sufi trend in the Diwan, especially asceticism, jihad, and the love of the Messenger and his family, may blessings and peace be upon them, and seeks to highlight the importance of Sufi studies in literature and criticism Literary today, as literary studies today witness an increased interest in this type of literature.